HEYZINE -BASED FLIPBOOK DIGITAL LEARNING MEDIA TO IMPROVE SCIENCE LEARNING OUTCOMES FOR FIFTH GRADE ELEMENTARY SCHOOL STUDENTS ON THE HUMAN RESPIRATORY SYSTEM - Erawati; Farida Istianah; Suryanti (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to develop a digital learning medium in the form of a Heyzine-based flipbook on the topic of the human respiratory system and to analyze the feasibility, practicality, and effectiveness of the media in improving the learning outcomes of fifth-grade elementary school students. This research employed a Research and Development method using the 4D development model consisting of four stages: define, design, develop, and disseminate. The study was conducted in two classes. trial class with twenty four students and dissemination class with thirty students. Data were collected through observation, interviews, expert validation questionnaires, student response questionnaires, and learning outcome tests. The data were analyzed using quantitative and qualitative descriptive analysis to determine the feasibility, practicality, and effectiveness of the developed media. The findings indicate that the Heyzine-based digital flipbook learning media achieved a very high level of feasibility according to evaluations by material and media experts. Furthermore, the developed media was considered practical for use in classroom learning and effective in improving students' learning outcomes on the human respiratory system topic. Therefore, the Heyzine-based digital flipbook can serve as an innovative learning medium to support science learning in elementary schools.